An analytical approach to test and design upper limb prosthesis. (September 2015) - Veer, Karan
Abstract In this work the signal acquiring technique, the analysis models and the design protocols of the prosthesis are discussed. The different methods to estimate the motion intended by the amputee from surface electromyogram (SEMG) signals based on time and frequency domain parameters are presented. The experiment proposed that the used techniques can help significantly in discriminating the amputee's motions among four independent activities using dual channel set-up. Further, based on experimental results, the design and working of an artificial arm have been covered under two constituents—the electronics design and the mechanical assembly. Finally, the developed hand prosthesis allows the amputated persons to perform daily routine activities easily.